Four new ent-kaurene diterpene glucosides from Mikania micrantha. (June 2017) - Dong, Li-Mei; Jia, Xu-Chao; Luo, Qing-Wen; Peng, Yi-Ming; Zhang, Qiang; Luo, Bi; Tan, Jian-Wen
Graphical abstract: Highlights: Four new and one known ent -kaurene diterpene glucosides were isolated. The new structures were elucidated by spectroscopic techniques. These compounds selectively showed antibacterial or cytotoxic activity. Abstract: Phytochemical study on the aerial parts of Mikania micrantha led to the isolation of four new ent -kaurene diterpene glucosides, β-d -glucopyranosyl-15α-(3-hydroxy-3-methylbutanoyloxy)-9β-hydroxy- ent -16-kauren-19-oate (1 ), β-d -glucopyranosyl-15α-(3-methylbutanoyloxy)-9β-hydroxy- ent -16-kauren-19-oate (2 ), β-d -glucopyranosyl-15α-(2-methylbutanoyloxy)-9β-hydroxy- ent -16-kauren-19-oate (3 ), β-d -glucopyranosyl-15α-(3-methyl-2-butenoyloxy)-9β-hydroxy- ent -16-kauren-19-oate (4 ), along with a known one, β-d -glucopyranosyl-15α-(3-hydroxy-3-methylbutanoyloxy)- ent -16-kauren-19-oate (5 ). Their structures were elucidated on the basis of extensive spectroscopic analysis. Compounds1 –4 are a group of C-9 hydroxylated ent -kaurene diterpene glucosides which is relatively rare in nature. These compounds were tested for their in vitro antibacterial activity against four assayed Gram-(+) and three Gram-(−) bacteria, while the results were poor. In addition, the in vitro growth inhibitory activity of these compounds against human cancer cell lines Hela, A549, HepG-2 and MCF-7, were also tested.